The role of communication in educational relations - Czerwiec, Karolina; Leżucha, Magdalena (Edukacja • Terapia • Opieka, 2024)
The art of communication is the ability to exchange information with people and to understand what information and feelings have been communicated. It engages us in some form of interpersonal communication to gain the ability to communicate with others. Communication is a key competence in everyone’s life. Communication in education is the foundation on which school relationships are built Open dialogue promotes an awareness of interest in the needs of others. We function in a world where other people are present, we need each other to fulfill our need for our own safety, friendship, or love, we need each other to achieve our goals. Meeting all these needs is not impossible without effective communication. Communication takes on a special importance in educational relationships, moreover, it is crucial in the teaching and learning process. Without effective communication, educational goals will not be achieved. This paper aims to present the role of effective communication in educational relationships, especially in the teacher-student context, and to show the consequences of a lack of effective communication in teaching.